2016
DOI: 10.1136/bmjopen-2016-011621
|View full text |Cite
|
Sign up to set email alerts
|

Costs of coordinated versus uncoordinated care in Germany: results of a routine data analysis in Bavaria

Abstract: ObjectivesThe efficiency of a gatekeeping system for a health system, as in Germany, remains unclear particularly as access to specialist ambulatory care is not restricted. The aim was to compare the costs of coordinated versus uncoordinated patients (UP) in ambulatory care; with additional subgroup analysis of patients with mental disorders.DesignRetrospective routine data analysis of patients with statutory health insurance, using claims data held by the Bavarian Association of Statutory Health Insurance Phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 27 publications
3
29
1
Order By: Relevance
“…This role of general medicine is also referred to as gatekeeping. Studies indicate that a well-functioning GP coordination might reduce, among others, healthcare spending and inequalities in the healthcare system [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This role of general medicine is also referred to as gatekeeping. Studies indicate that a well-functioning GP coordination might reduce, among others, healthcare spending and inequalities in the healthcare system [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison with other studies carried out within the German healthcare system may aid interpretation of Freytag et al's findings. In an analysis of Bavarian data from the first quarter of 2011, my co-authors and I compared 1 229 372 patients who were referred to specialists by their GPs with a similarly high number of patients who consulted specialists on their own initiative (5). We found that coordination of care is cost efficient-all the more so in older patients and in With this comprehensive approach, general medicine helps to ensure effective healthcare of the population.…”
Section: Comparison With Other Studiesmentioning
confidence: 95%
“…Studies indicate that a well-functioning GP coordination might reduce, among others, healthcare spending and inequalities in the healthcare system [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%